Neuroplastic effects of transcranial alternating current stimulation (tACS): from mechanisms to clinical trials - Agboada, Desmond; Zhao, Zhihe; Wischnewski, Miles (Frontiers in Human Neuroscience, 2025)
Transcranial alternating current stimulation (tACS) is a promising non-invasive neuromodulation technique with the potential for inducing neuroplasticity and enhancing cognitive and clinical outcomes. A unique feature of tACS, compared to other stimulation modalities, is that it modulates brain activity by entraining neural activity and oscillations to an externally applied alternating current. While many studies have focused on online effects during stimulation, growing evidence suggests that tACS can induce sustained after-effects, which emphasizes the potential to induce long-term neurophysiological changes, essential for therapeutic applications. In the first part of this review, we discuss how tACS after-effects could be mediated by four non-mutually exclusive mechanisms. First, spike-timing-dependent plasticity (STDP), where the timing of pre- and postsynaptic spikes strengthens or weakens synaptic connections. Second, spike-phase coupling and oscillation phase as mediators of plasticity. Third, homeostatic plasticity, emphasizing the importance of neural activity to operate within dynamic physiological ranges. Fourth, state-dependent plasticity, which highlights the importance of the current brain state in modulatory effects of tACS. In the second part of this review, we discuss tACS applications in clinical trials targeting neurological and psychiatric disorders, including major depressive disorder, schizophrenia, Parkinson’s disease, and Alzheimer’s disease. Evidence suggests that repeated tACS sessions, optimized for individual oscillatory frequencies and combined with behavioral interventions, may result in lasting effects and enhance therapeutic outcomes. However, critical challenges remain, including the need for personalized dosing, improved current modeling, and systematic investigation of long-term effects. In conclusion, this review highlights the mechanisms and translational potential of tACS, emphasizing the importance of bridging basic neuroscience and clinical research to optimize its use as a therapeutic tool.